Culturally specific British idioms in English - Tsypkina Mariia (My University, 2023)
The field of research is linguistics, phraseology, lexicology and terminology, as well as cultural and historical studies. These spheres of linguistics have been of interest for scholars such as David Crystal, Steven Pinker, Mykhailo Kocherhan and others. The object of this paper is the idiomatic expressions in British English. The subject of this paper is the idioms containing Briticisms that denote British currency. The paper consists of the theoretical part of the research, where the topics of definition of idioms, their cultural peculiarities, the notion of Briticisms and the themes of British culture are discussed, and the practical part of the research, which explores the theme of currency in the scope of the culturally specific British idioms, the change of focus from the cultural aspect of those idioms and the frequency of their usage in modern speech.
Keywords: British idioms; British English